"Embedded Racism" In Japan's Official Registry Systems: Towards A Japanese Critical Race Theory - Arudou, Debito (Penerbit Universiti Sains Malaysia (USM Press), 2014)
Critical Race Theory (CRT), grounded in American legal theories of power and dominance, has been increasingly applied to other countries to analyse racialised power relationships between social groups. Applying CRT to Japanese society, where "racism" is officially denied as a factor in the systemic differentiation of peoples into a dominant majority and disenfranchised minorities, nevertheless reveals racialised paradigms behind deciding who is a "member" of society (as in a citizen) and who is not (as in, a non-citizen), systematically allocating privilege to people with "Japanese blood." This research focuses on recent changes to Japan's official registry systems vis-à-vis non-citizens. Historically, the Family Registry (koseki) and the Resident Registry (jūmin kihon daichō) have employed biological conceits to give systemic advantages (in terms of citizenship, employment, access to social welfare and official recognition as residents and family members) to "Wajin" (Japan's dominant social group with "Japanese blood") over "Non-Wajin." Although the Resident Registry system was amended in July 2012 to allow equal registry of noncitizens, this research finds under CRT methodology that the dominant Wajin majority did not further enfranchise or cede power to the disenfranchised non-citizen minority. The reforms were merely cosmetic changes to a segregating system that remains largely intact in scope and enforcement.